The materiality of Middle English anchoritic devotion - Sauer, Michelle M., 1972-; Bledsoe, Jenny C. (Early Middle English (Series), 2021)
Anchorites and their texts, such as Ancrene Wisse, have recently undergone a reevaluation based on material circumstances, not just theological import. The articles here address a variety of anchoritic or anchoritic-adjacent texts, encompassing guidance literature, hagiographies, miracle narratives, medical discourse, and mystic prose, and spanning in date from the eighth through the fourteenth centuries. Exploring reclusion and materiality, the collection addresses a series of overlapping themes, including the importance of touch, the limits of religious authority, and the role of the senses.